The Family Health Strategy coverage in Brazil: what reveal the 2013 and 2019 National Health Surveys - Giovanella, Ligia; Bousquat, Aylene; Schenkman, Simone; de Almeida, Patty Fidelis; Sardinha, Luciana Monteiro Vasconcelos; Vieira, Maria Lúcia França Pontes (Ciência & saude coletiva, 2021)
This paper examines the evolution of Brazil's Family Health Strategy coverage from the findings of the 2013 and 2019 National Health Survey censuses. Indicators included Family Health Clinic coverage of residents and households, frequency of visits by Community Health Workers, and usual source of care, all stratified by rural and urban areas, Brazilian regions, states, education of the household head, and income quintile. In 2019, 60.0% of households were enrolled in a Family Health Clinic, and population coverage was 62.6%. Coverage was higher in rural than in urban areas in the Northeast and South regions. Between 2013 and 2019, coverage increased by 11.6%, while monthly health worker visits decreased. Coverage was highest among the most vulnerable population, as defined by the household head education level or by the family income. Availability of usual source of care was highest among those enrolled in a Family Health Clinic. The 2019 National Health Survey findings confirm that Brazil's Family Health Strategy continues to be an equitable policy and the main SUS' Primary Health Care model. However, recent changes in the national policy guidance, which are weakening the community approach and the priority given to the Family Health Strategy Program, may jeopardize those gains.